2020
DOI: 10.5194/bg-17-3471-2020
|View full text |Cite
|
Sign up to set email alerts
|

On giant shoulders: how a seamount affects the microbial community composition of seawater and sponges

Abstract: Abstract. Seamounts represent ideal systems to study the influence and interdependency of environmental gradients at a single geographic location. These topographic features represent a prominent habitat for various forms of life, including microbiota and macrobiota, spanning benthic as well as pelagic organisms. While it is known that seamounts are globally abundant structures, it still remains unclear how and to which extent the complexity of the sea floor is intertwined with the local oceanographic … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
34
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 21 publications
(37 citation statements)
references
References 74 publications
(101 reference statements)
3
34
0
Order By: Relevance
“…Atlantic (Rice et al, 1990) or the Faroe Shetland channel where sponges were observed in regions with intensified internal wave activity and associated with pronounced changes in temperature (Davison et al, 2019). Such conditions have also been found on seamounts and canyons, where sponge aggregations have been observed in areas of critical slope in the Arctic (Schulz Bank seamount; Busch et al, 2020) and the Azores (Rainbow Basin;van Haren et al, 2017). Based on our data we can only link the environmental fluctuations to the presence of tidal currents.…”
Section: Environmental Conditions On the Scotian Shelfmentioning
confidence: 55%
See 1 more Smart Citation
“…Atlantic (Rice et al, 1990) or the Faroe Shetland channel where sponges were observed in regions with intensified internal wave activity and associated with pronounced changes in temperature (Davison et al, 2019). Such conditions have also been found on seamounts and canyons, where sponge aggregations have been observed in areas of critical slope in the Arctic (Schulz Bank seamount; Busch et al, 2020) and the Azores (Rainbow Basin;van Haren et al, 2017). Based on our data we can only link the environmental fluctuations to the presence of tidal currents.…”
Section: Environmental Conditions On the Scotian Shelfmentioning
confidence: 55%
“…Water column mixing will result in an increased availability of nutrients from the deeper water masses toward the surface (Townsend et al, 2006), triggering primary productivity and increased benthic-pelagic coupling (Ji et al, 2006). Topography-hydrography interactions can also influence biogeochemistry and microbiology either by mixing or by resuspension as described above, which can result in different sponge associated microbial communities defined by the surrounding near-bed environment (Busch et al, 2020). This mixing will indirectly promote an increased vertical flux and therefore food supply to the sponge grounds and their associated fauna, as was also observed in the Gulf of Mexico and on the Namibian margin (Mienis et al, 2012;Hanz et al, 2019).…”
Section: Eventsmentioning
confidence: 99%
“…A proposed candidate phylum for MBFAs is Poribacteria, a unique and abundant phylum in HMA sponges [46], since a positive relation between MBFA concentration and Poribacteria abundance was found across several sponge species [44]. Metagenome analyses showed that Poribacteria are a prominent phylum in G. barretti [47,48], but are rare or even absent in G. hentscheli [49], which shows a dominance of Acidobacteria, Chloroflexi, and Proteobacteria, phyla that are also abundant in G. barretti [47,48]. This suggests that either the MBFAs belong to one of the above-mentioned phyla, or that the MBFAs are shared among microbial phyla, as their chemotaxonomic resolution is lower compared to genomic analysis.…”
Section: Bacterial Fasmentioning
confidence: 99%
“…In order to examine the microbial diversity in the studied sponges, 13 individuals of V. pourtalesii were collected from Sambro Bank and 13 of S. rosea from Schulz Bank. The sample processing procedure is described in detail elsewhere (Busch et al, 2020(Busch et al, , 2021; see also these references for data availability). Briefly, from each sponge individual chunks of tissue were subsampled, rinsed and frozen at −80 • C until DNA extraction.…”
Section: Diversity and Functional Gene Analysis Of Associated Microbiotamentioning
confidence: 99%